Right to health in the court of justice: demand for oncology drugs - Souza, Ítala Paris de; Bellato, Roseney; Araújo, Laura Filomena Santos de; Almeida, Karla Beatriz Barros de; Nepomuceno, Marly Akemi Shiroma; Mufato, Leandro Felipe (Rev Rene, 2012)
Malignant neoplasm is the second cause of death of Brazilians as well as the people around the world. The objective was to study decisions in the judiciary system of Mato Grosso State regarding the demand of rights to health for cancer affected people and their access to drugs. Documental qualitative methodological approach was used and resulted into the following subcategories: types of medication and ways of naming it; disease situation and chosen drug; lawsuit type; arguments; justification of the demand by lawsuit author; negative decisions from the magistrate; reasons and justifications of the magistrate´s decisions; visibility given to defendant named in the lawsuit. The research highlights the state´s negative response to offer cancer affected people specific drugs which are not included in its policy and in turn, those people enter a lawsuit against the state in order to occasionally soothe their problems. Their requests are taken into consideration by the magistrate despite the state´s opposing opinion in giving them the right to health.